Elderly individuals living by themselves: knowledge and measures to prevent the novel coronavirus - Darlene Mara dos Santos Tavares; Nayara Gomes Nunes Oliveira; Gianna Fiori Marchiori; Mariana Silva Freitas Guimarães; Lenniara Pereira Mendes Santana
Objective: to describe the occurrence of COVID-19 and the health services used by elderly individuals living by themselves; identify the knowledge held by elderly individuals regarding the transmission, signs and symptoms of COVID-19, as well as factors associated with poor knowledge of preventive measures according to sociodemographic and clinical variables. Method: cross-sectional survey conducted by telephone or mobile with 123 elderly individuals living by themselves in the Health Macro-Region of Triângulo Sul in the state of Minas Gerais, Brazil. Descriptive analysis was performed along with bivariate and multiple linear regression (p<0.05). Results: most elderly individuals did not present COVID-19 signs and symptoms (97.5%), were aware of how it is transmitted (86.6%), and of its signs and symptoms (90.8%). The elderly individuals were familiar with four preventive measures on average. After social distancing began, 85.7% of them left home and implemented three preventive measures on average, the most frequent of which was the use of face masks (99.0%). Being a man (p=0.001), 80 years old or older (p=0.045), and having fewer years of schooling (p=0.010) were associated with having less knowledge regarding the COVID-19 preventive measures. Conclusion: the elderly individuals were knowledgeable on COVID-19, but did not implement all the preventive measures. Male elderly individuals living by themselves with a low educational level are more vulnerable to COVID-19.